2019
DOI: 10.3920/jiff2017.0061
|View full text |Cite
|
Sign up to set email alerts
|

Alternative protein production for animal feed:Musca domestica productivity on poultry litter and nutritional quality of processed larval meals

Abstract: The productivity of Musca domestica larvae reared on poultry litter and the nutritional parameters of insect meal as an animal feed ingredient have been evaluated. In laboratory bioassays, a seeding density of 0.32 g eggs/kg wet weight litter produced maximal yields of >50 g of naturally egressing larvae/kg substrate. Substrate composition and moisture content were critical determinants for insect development and generally litter wetted to water holding capacity (approx. 23% dry weight) was optimal for larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
3
16
0
1
Order By: Relevance
“…Unidentified fatty acids in HF larvae or pupae were relatively high (7.2-8.5%) comparing with other insects [19]. Since the composition of unidentified fatty acids in HF larvae reached 15% and depended on sources of poultry litter as rearing substrates for HF larvae [12], these unidentified fatty acids seemed to be derived from pig manure used for rearing the larvae. Chitin, a linear homopolymer of β(1-4)-linked N-acetylglucosamine units, a major constituent of insect cuticles, was thought to influence growth reduction in marine fish because of its difficulty in digestion [34].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Unidentified fatty acids in HF larvae or pupae were relatively high (7.2-8.5%) comparing with other insects [19]. Since the composition of unidentified fatty acids in HF larvae reached 15% and depended on sources of poultry litter as rearing substrates for HF larvae [12], these unidentified fatty acids seemed to be derived from pig manure used for rearing the larvae. Chitin, a linear homopolymer of β(1-4)-linked N-acetylglucosamine units, a major constituent of insect cuticles, was thought to influence growth reduction in marine fish because of its difficulty in digestion [34].…”
Section: Discussionmentioning
confidence: 89%
“…The housefly (Musca domestica) can yield animal protein in the biodegradation of organic waste [4], such as pig manure [5][6][7][8][9][10], cattle manure [11], poultry litter [12], and food waste [13]. The larvae obtained from these systems are alternative feed ingredients that are rich in nutrients from within the human food chain without the need to harvest part of the wild marine ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reveal the efficiency of different methods to eliminate microorganisms in insect biomass destined for food. Fitches et al [44] did not find Salmonella, and Enterobacteria were found in smaller quantities than the detection limit (< 10 CFU) in M. domestica larvae processed with water at temperatures of 50-80 °C, followed by heating of 65-90 °C. On the other hand, Kashiri et al [79] determined that high hydrostatic pressure can be effective in some natural microorganisms in H. illucens biomass such as mold and yeast, and in inoculated E. coli, but with limited effect on total aerobic mesophilic bacteria count.…”
Section: Effect On Pathogenic Organismsmentioning
confidence: 91%
“…Although the potential inactivation/reduction of some microorganisms by the action of fly larvae, Salmonella sp., and Enterococcus faecalis can be transferred to H. illucens larval biomass [38,87]. However, Fitches et al [44] did not detect Salmonella in M. domestica larvae fed on poultry litter (chicken manure and sawdust), but Enterobacteria were found at higher concentrations on larvae (5.2 log CFU g −1 ).…”
Section: Effect On Pathogenic Organismsmentioning
confidence: 96%
“…Examples of substrates that may be used in breeding house fly larvae include animal offal, poultry manure, pig manure, cattle intestines and rumen contents, cattle blood and wheat bran, bovine blood and intestine contents, hatchery and wheat bran, fish intestines and a mixture of egg contents, and all sorts of food waste. (Odesanya et al, 2011;Ossey et al, 2012;Čičková, et al, 2012;Zhu et al, 2012Zhu et al, , 2015Niu et al, 2017;Fitches et al, 2018;Hashizume, 2019).…”
Section: Mass Production Of Larva and Pupamentioning
confidence: 99%